PENGAMBILAN CHROM PADA LIMBAH ELEKTROPLATING - Firda Herlina (Universitas Lambung Mangkurat, 2013)
Tanning industry wastewater includingliquid wasterequires special carebecausethe rest of the ingredients Tanning perishable sand the amount of metal ions that can cause pollution and danger toliving things. Electrocoagulation process has be enevaluated as an alternative technology to reduce the concentration of chromium from Tanning effluent. Elektrokoagulator electrocoagulation performed in a batchstirred by using a pair of metal electrodes with dimensions of technical 100-25-0.5mm. By variation of the length of time from 15 minutes to astirring 75 min, the variation speed of 120 rpm stirring to 600 rpm, and the variation of the degree of acidity of 4-8. The results showed that the concentration of chromiumin the waste water can be reduced by using electrocoagulation of 2435.714 mg/Lup to2.84 mg/L.